Integrating anticipatory action in disease outbreak preparedness and response in the humanitarian sector - Rachel Lowe; Meghan Bailey; Tilly Alcayna; Franziska Kellerhaus; Leo Tremblay; Chloe Fletcher; Rachel Goodermote; Mauricio Santos-Vega; Juan Chaves-Gonzalez; V. Bhargavi Rao (BMJ Global Health)
In the humanitarian sector, anticipatory action entails acting ahead of predicted hazardous events to prevent or mitigate potential impacts and needs. It leverages early warnings to bridge preparedness and response, with a core principle being the provision of ex-ante emergency funding for preagreed early actions. Traditionally applied to extreme climatic events, there is growing interest in integrating anticipatory action into disease outbreak preparedness and response. We present an analytical framework for trigger development for climate-sensitive infectious disease outbreaks based on a review of existing and emerging practices from the Red Cross Red Crescent Movement, United Nations agencies and Médecins Sans Frontières since 2014. We propose that, depending on data availability, there are four broad approaches for trigger development. First, the humanitarian sector could scale up the release of prearranged funding based on real-time surveillance data (eg, suspected cases) while other emergency funding is secured. Second, the humanitarian sector could take advantage of weather forecasts and seasonal climate forecasts to anticipate outbreaks linked to extreme climatic events, anomalous climatic conditions or highly suitable climatic conditions. Third, to extend the lead time available for intervention, the humanitarian sector could use observed environmental and socioeconomic transmission risk factors (eg, population displacement, overcrowding, presence of vectors, weather changes) in combination with real-time surveillance data to improve early detection or curb a rapid increase in cases, while other emergency funding is secured. Fourth, data-driven outbreak forecasting using seasonal forecasts can help extend the lead time further to make informed decisions about future risks. We present examples and discuss the trade-offs between approaches. As anticipatory action for outbreaks becomes established, we expect that future applications will integrate all four approaches.